Performance assessment of Baznef model in health promotion of patients with cancer - Mohammad Hossein Taghdisi; Nasrin Abdi; Sirous Shahsavari; Maryam Khazaeipool (Iran University of Medical Sciences, 2011)
Background and Aims: Cancer occurs when cells divide uncontrollably. These abnormal cells can invade nearby tissues or travel to distant sites by entering the bloodstream or lymphatic system. Incidence rate of cancer during the last 50 years has increased constantly. Nutrition, physical activity and hope are important factors in cancer. However, patients do not have correct knowledge and proper attitude regarding these important factors. The aim of this study is performance assessment of basnef model in health promotion for pations with cancer in Sanandaj city.Material & Methods: This study is a randomized controlled trial. Knowledge and attitude questionnaires in basnef model and HHI questionnaire was completed before and after intervention in two case and control groups (n: 50) and knowledge and attitude questionnaire in patients family in two case and control groups (n: 50).The educational and promotional intervention for patients and their families in case groups as a face to face method and individually with PBL method was accomplished. Data was analyzed by use of spss and Chi -square tests and co-variance analysis.Results: The mean score for knowledge in case group patients was significantly more than controls group (P<o.ooo). Intervention also resulted in better attitude in case group patient) P<0.000).A significant difference was not found in subjective norms mean score (P<0.12) and enabling factors (P<0.08) in two groups. The hope mean scores in case group patients was significantly more than control group (P<0.008). The knowledge mean scores also in family case group was more than control group family (P<0.001) and intervention resulted in better attitude situation in case group family (P<0.000).  Conclusions: Educational intervention is effective in increasing knowledge and improvement of attitude and also promotion of hope in cancer patients and their families. So preper educational methods (e.g. PBL), with active participation of patients and families to promote quality of life is recommended.